The key elements of classroom management : managing time and space, student behavior, and instructional strategies - McLeod, Joyce, 1940- (Association for Supervision and Curriculum Development, 2003)
All teachers know that a well-managed classroom is the cornerstone of a strong instructional program, but many are uncertain where they should focus their energies. In The Key Elements of Classroom Management, three veteran teachers show how teachers can make real improvements in their classroom by concentrating on basic skills in three critical areas: . Managing Time and Space. Joyce McLeod shares techniques to help K-12 teachers arrange the classroom, organize schedules, pace the year's curriculum, and manage administrative tasks. . Managing Student Behavior. Jan Fisher focuses on preventing conflicts and disruptions by teaching students responsibility, self-management, and problem-solving and decision-making skills. . Managing Instructional Strategies. Ginny Hoover describes various research-based instructional methods, identifying the advantages and disadvantages of each. The authors combine insights gleaned from extensive experience with step-by-step discussions of practical strategies. Any teacher who has struggled with the day-to-day challenges of the classroom will find an abundance of proven techniques for creating an orderly, caring, and efficient environment that supports successful teaching and learning.